Role of leukemic stem cells in the chronic myeloid leukemia pathogenesis - Sviezhentseva, I (Annals of Mechnikov's Institute, 2020)
The presence of leukemic stem cells (LSC) in the bone marrow of patients with chronic myeloid leukemia (CML) is the cause of relapses as a result of the treatment with chemotherapeutic agents and target therapy drugs. This is due to the ability of LSC to attach itself to the microenvironment cells and to remain at rest for a long time. Vascular and osteoblasts niche play a very important role in this process. However, for being in G0 phase LSC have direct contact with the cellular elements of bone marrow microenvironment. So LSK contact with mesenchymal cells of bone marrow using the appendixes, connecting components invaginations and lint. The cadherins and integrins are important in the interaction of osteoblasts niche. They are able to activate intracellular signaling cascades that provide resting state of LSK. In addition, a bone marrow niche provides changes of LSC oxidative metabolism, which also plays an important role for cell entry into the G0 phase. Further, LSC also have certain physiological properties, which play an important role in the drug resistance formation, particularly drugs with targeted actions - tyrosine kinase inhibitors. LSK characterized by a high level of BCR-ABL expression and their population can have a lot of point mutations in the bcr-abl gene in the same patient. This leads to the fact that the taken medicines dose does not act against LSK, reducing the number of a whole leukemic cells clone. However, complete LSC elimination from the the patient’s bone marrow need search the main differences between the LSC and normal HSC. After the literature analysis it was found that LSC have several significant differences such as the ability to cause leukemia during the transplantation to immunodeficient animals, this leukemia is morphologically and phenotypically similar to the original tumor, in addition the LSC can be transmitted from animal to animal. In addition, the LSC is also characterized by the mutations presence in the genes of kinase domains, transcription factors and tumor suppressors (genes of growth factors FLT3, C-KIT, genes K-RAS and N-RAS, mutations in genes STAT5A, TP53, AML1, RB1, MYC, p16 / NK4a, ENV1). Now the most important role in LSK biology research takes studying of signaling cascades involved in the processes of cell activity. This key molecule of cell signaling pathways can become targeted agents that may be used for the elimination of LSC from the patient bone marrow. However, it is necessary to distinguish the molecular cascades that are inherent to all bone marrow stem cells from LSC specific intracellular signal transmittors. Common to the LSC and HSC are the following signaling pathways: Wnt/β-catenin, Sonic Hedgehog and Noch signaling pathways. Moreover, there are signaling cascades that are specific only for LSC. They are charecterized by the exclusive expression of Alox5, AHI-1 and NFκB genes. In addition, the LSC are also characterized by the increased expression of AVSV-1 and ABCG-2 transporters, providing the evacuation of the cell chemotherapeutic drugs. LSC are characterized by the decreased expression of Oct-4, which ensures the supply of drugs to cells. The article also highlights the key therapeutic tactics that can be used to eliminate the recurrence of CML associated with the presence of LSC, which remain at rest for a long time, in the bone marrow of patients. The first tactic is elimination of LSC using the targeted drugs that operate solely on the target molecule in leukemic cells. The second approach is a direct administration of drugs to a patient that could promote a permanent state of rest for LSC in order to prevent relapses